FAKTOR-FAKTOR SOSIAL EKONOMI DAN KESEHATAN MASYARAKAT KAITANNYA DENGAN MASALAH GIZI UNDERWEIGHT, STUNTED, DAN WASTED DI INDONESIA: PENDEKATAN EKOLOGI GIZI - Dian Hani Ulfani; Drajat Martianto; Yayuk Farida Baliwati (Jurnal Gizi dan Pangan, 2011)
Malnutrition is an ecological problem in the sense influenced by various aspects, as explained in the framework of UNICEF (1988). Indonesia as developing country at present still faced such a problem. Eco-nutrition is important to understand related factors affecting malnutrition in Indonesia to find out more effective programs. Eco-nutrition have three key areas : public health (access to quality water, sanitation and health services), socio economic (livelihood assets) and malnutrition. The purpose of this research was to study the linkages between socioeconomic and public health factors with the problem of underweight, stunted, and wasted in Indonesia.This research was conducted using cross-sectional study design, analyzed the 424 districts/cities in Indonesia. Data prevalence of underweight, stunted, wasted, level of education and public health factors (access to quality water, hygiene behavior, utilization of Posyandu, complete immunization coverage, incidence of diarrhea, and the incidence of acute respiratory infections (ARI) obtained from Riset Kesehatan Dasar (Riskesdas ) 2007. Socio-economic data (level of poverty and GDP/capita) obtained from the Central Statistic Agency (BPS). Statistical test of Pearson correlation and stepwise linear regression method were implemented to understand factors affecting underweight, stunted, wasted and correlation among variables. The study shows that factors affecting underweight were educational level, poverty level, hygiene behavior and use of Posyandu. While factors affecting stunted were GDP/capita, education level, poverty level, hygiene behavior, and utilization of Posyandu. Factors affecting wasted were hygiene behavior, utilization of Posyandu and complete immunization.